Characterization of Neoantigen Load Subgroups in Gynecologic and Breast Cancers - Yue Zhu; Xiaowei Meng; Xinjia Ruan; Xiaofan Lu; Fangrong Yan; Fei Wang (Frontiers in Bioengineering and Biotechnology, 2020)
ObjectiveAlthough gynecologic and breast (Pan-Gyn) cancers share a variety of similar characteristics, their response to immunotherapy is different. Immune checkpoint inhibitor therapy is not effective in all patients, while neoantigen load (NAL) may be a predictive biomarker. However, the selection of a NAL cutoff point and its predictive effect remain to be elucidated.MethodsWe divided 812 Pan-Gyn cancer samples from The Cancer Genome Atlas into three groups based on 60 and 80% of their load percentile. We then correlated the identified NAL subgroups with gene expression, somatic mutation, DNA methylation, and clinicopathological information. We also characterized each subgroup by distinct immune cell enrichment, PD-1 signaling, and cytolytic activity. Finally, we predicted the response of each subgroup to chemotherapy and immunotherapy.ResultsAcross Pan-Gyn cancers, we identified three distinct NAL subgroups. These subgroups showed differences in biological function, genetic information, clinical variables, and immune infiltration. Eighty percent was identified as a meaningful cutoff point for NAL. In all patients, a higher NAL (top 20%) was associated with better overall survival as well as high immune infiltration and low intra-tumor heterogeneity. Furthermore, an interesting lncRNA named AC092580.4 was found, which was associated with two significantly different immune genes (CXCL9 and CXCL13).ConclusionsOur novel findings provide further insights into the NAL of Pan-Gyn cancers and may open up novel opportunities for their exploitation toward personalized treatment with immunotherapy.